Valenthina Br Purba KONTRIBUSI PENDAPATAN PEREMPUAN TERHADAP EKONOMI KELUARGA DI BERASTAGI TANAH KARO - Purba, Valenthina Br; Pramana, S.IP., M.A., Gede Indra; S.IP., M.Si., Dr. Tedi Erviantono, (Jurnal Nawala Politika, 2023)
The majority of the livelihoods of the people of Berastagi Karo Regency are farming, but some residents of Berastagi work as traders at the Berastagi market center. Farming involves both men and women while working. Women's contributions are needed by farmers, this becomes a mutually beneficial reciprocity. Women's income is needed to fulfill the family's economy because the cost of living and basic expenses have soared so that several supporting factors are needed, such as the contribution of women in earning a living. In the economic field, Berastagi women occupy a strategic role in meeting the economic needs of their families. Many jobs done by men are also done by women in order to fulfill the necessities of life such as farming and trading. If it is associated with the culture of the Karo tribe, a woman is indeed required to work and take responsibility for the family economy and for her children. Working for women is part of the role that must be carried out as a responsibility for the family and a basis for obedience to husbands, because "it has been bought". However, the economic and public roles bestowed upon them by the women of the night have made them realize that the necessities of life are highly dependent on income.   Keywords: Income, Contribution of Women, Economy, Berastagi